279 Preparing Foundation Trainees for Surgical On-Calls. (12th October 2021) - Boyle, M; Thu, K; Mroczek, T; Scicluna, M; Byrne, A
Abstract: Aim: Foundation trainee feedback has highlighted low levels of confidence with the prospect of surgical on-calls. Key areas of concern are assessing and managing the acute surgical patient, identifying which patients need an operation and having the technical skills to competently assist in theatre. This lack of confidence prevents trainees engaging in an educational and rewarding rotation. We have designed and facilitated a day of robust workshops, addressing these key educational needs. Method: Pre and post course questionnaires assessed the efficacy of teaching. Lectures on the assessment and management of acute surgical patients in general surgery, urology and trauma and orthopaedics were delivered by core surgical trainees. A named consultant oversaw quality assurance. Addressing the technical skills development need, an afternoon of surgical skills workshops covered, suturing, knot tying, laparoscopic principles, and theatre etiquette. Small groups of trainees rotated through each workshop, delivered by senior specialty trainee registrars, to ensure high fidelity training Results: Trainees rated themselves in key areas pre and post course on a scale from 1-5. Pre course, 66% of trainees scored 3+ in "confidence in managing a surgical patient on-call". This rose to 100% post course. Similarly; "Confidence in decision making regarding whether a patient should proceed to theatre" increased from 37.5% to 93.7%. "Suturing skills" improved from 37.5% to 100%. Conclusions: All trainees that attended the course displayed marked improvement in their confidence and competence. We feel this course or similar should be incorporated into the foundation teaching program locally and has scope to be expanded regionally.